APLIKASI ZPT NOVELGRO ALPHA DAN POC BIO SUGIH TERHADAP PERTUMBUHAN BIBIT ADENIUM (Adenium obesum var. Fadia) - Bambang Supriyanto (Universitas 17 Agustus 1945 Samarinda, 2012)
The propose of research was to know interaction between the Novelgro Alpha plant growth regulator and the Bio Sugih liquid organic fertiliser application on the growth of Adenium (Adenium obesum var. Fadia), and to find the best concentration of both Novelgro Alpha and Bio Sugih that effect the best growth of Adenium seedling. The research conducted from July until October 2008 in the greenhouse (OECF Integrated Laboratory) of Agricultural Faculty, Mulawarman University, Samarinda. The research was arranges in randomized completely design (RCD) in factorial which consist two factors with five replications. The first factor was consentration of Novelgro Alpha that consist three levels, namely n0 (control), n1 (1.0 mL L-1 solution), and n2 (2.0 mL L-1 solution). The second factor was Bio Sugih that consist three levels, namely p0 (control), p1 (1.0 mL L-1 solution) and p2 (2.0 mL L-1 solution). Result of this research showed that interaction between Novelgro Alpha and Bio Sugih is significantly different on the plant height increment at the third, the fourth, the fifth, and the sixth two-week after treatment, the increment of leave number at the first, the fourth two-week, the fifth two-week, and the sixth two-week after treatment, the increment of stem diameter at the second, the fourth, the fifth, and the sixth two-week after treatment; the increment of leaf area and leaf thickness. Novelgro Alpha is also significantly different on the plant height at the third, the fourth, the fifth, and the sixth two-week after treatment; the increment of stem diameter at the fourth, the fifth, and the sixth two-week after treatment; the increment of leave number, leaf area and leaf thickness. Meanwhile, the Bio Sugih liquid organic fertilizer was significantly different on the increment of leave number at fourth and the sixth two-week after treatment.